Effect Of Digital Taxation On Revenue Generation: The Mediating Role Of Taxpayer Awareness - Mustapha, Bojuwon; Akomolafe, Olayiwola Samson; Omolade, Bamisaye Theresa; Bosede, Abiloro Rafiyat; Moronke, Lawal Adenike (Journal of Accounting Inaba, 2025)
This study examines how taxpayer awareness mediates the relationship between digital taxation and revenue generation in Nigeria. PLS Structural Equation Modelling (SEM) was used to analyze data from tax practitioners and economists to assess the impact of mechanisms of digital taxation on public revenue outcomes. The results indicate that computerized tax law negatively and significantly affects taxpayer awareness and revenue collection, implying that rigid or poorly explained tax law reduces tax engagement and budget performance. In addition, digital tax rates have a positive and significant impact on both revenue collection  and taxpayer awareness, suggesting that open and well-structured digital tax regimes increase compliance and revenue. Taxpayer awareness is also having a positive and significant impact on revenue collection. In addition, the indirect impact of digital tax rates on revenue realization via awareness is negative, whereas the mediated impact of digital tax policies is significantly positive. The study concludes that transparent digital tax policies and high public awareness are key to improving Nigeria's digital tax revenue performance and recommends reforms to sustain this momentum.